(untitled) (Journal of Engineering, 2025)
One zinc-27 % aluminum alloy (ZA-27) with excellent corrosion resistance and high hardness is ZA-27, making it suitable for industrial applications such as vehicle parts. The alloy works better in tough mechanical conditions because it has carbide particles, like SiC or TiC, added to it, which make it harder, more resistant to wear, and improve its internal structure. Using Minitab statistical software, the design of experiments (DOE) was utilized to conduct studies with a statistical two-level factorial experimental design. The effect of three parameters, SiC particles percentage (X1), stirring speed (X2), and stirring time (X3), was studied on the tensile characteristics of the SiC-enhanced ZA-27. The ingot was smelted using the stir-casting process to make a composite material. Then, varied percentages of SiC particles (0 and 5 wt%), speeds (300 and 900 rpm), and stirring times (30 and 60 min.) were utilized to stir the molten metal. The regression results showed that there was a satisfactory fit of the model variability for both SiC particles (X1) and stirring speed (X2). The p-value for each parameter was less than 0.005, which is statistically significant. It was determined that the factors X1 = 5 wt.% X2 = 900 rpm, and X3 = 60 minutes could provide the greatest tensile strength of 465 MPa. The tensile strength (465.5 MPa) obtained in practice using the values of X1, X2, and X3 calculated by the programs is almost identical to that obtained practically.